ARE FARMERS USING MOBILE APPLICATION FOR AGRO-ADVISORY SERVICES: EVIDENCE FROM DEVCHULI MUNICIPALITY, NAWALPARASI EAST - Birendra Tiwar; Amrit Dumre; Mahesh Jaishi (Big Data in Agriculture)
Mobile-based application, an important tool of Information Communication Technology (ICT) has become one of the integral parts of agro-advisory services in Nepal. This paper aims to explore the factors affecting the adoption of mobile-based applications for agro-advisory services in Devchuli Municipality Nawalpur. 96 farmers from 8 wards of the municipality were selected randomly and interviewed by using a semi structured close-ended questionnaire. Descriptive statistics, index score ranking method, and binary logistic regression model were used for data analysis. It was found that respondents use mobile applications to receive information on cultivation practice, plant protection, post-harvest, modern agriculture technology, market, weather forecast, and information regarding insurance, subsidy, and training. Age and year of schooling significantly affect the adoption of mobile-based applications. Mobile applications seem as one of the potent tools to strengthen the agro-advisory services in the municipality.